2018
DOI: 10.2106/jbjs.17.00018
|View full text |Cite
|
Sign up to set email alerts
|

Early Clinical and Radiographic Outcomes of Trabecular Metal Total Ankle Replacement Using a Transfibular Approach

Abstract: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 48 publications
0
34
1
Order By: Relevance
“…Radiolucent lines are a cause for concern after TAR. Barg et al reported a high rate of radiolucent lines in the tibial and talar-implant interface of 34.5% and 12.7% respectively [24]. Interestingly, we observed radiolucent lines in 10% of the patients.…”
Section: Discussionmentioning
confidence: 40%
“…Radiolucent lines are a cause for concern after TAR. Barg et al reported a high rate of radiolucent lines in the tibial and talar-implant interface of 34.5% and 12.7% respectively [24]. Interestingly, we observed radiolucent lines in 10% of the patients.…”
Section: Discussionmentioning
confidence: 40%
“…Furthermore, the medial border of the talar dome had a smaller radius of curvature than that of lateral border [10, 11]. And these observations have been copied in the design of some ankle systems [1214]. However, the concept of the fixed rotation axis of the talocrural joint contradicted with the coupled behavior of ankle joint complex, and several later results in vitro or vivo [4, 1518].…”
Section: Introductionmentioning
confidence: 99%
“…Short-term clinical follow-up (range 24.0-39.8 months) of the Zimmer TM Ankle, introduced in 2012, has not revealed any occurrences of polyethylene fracture for 55 TAAs performed by a single surgeon. 5 A single revision of the TM Ankle has been reported in the published literature; an analysis of that case attributed the cause of revision to component malpositioning. 13 There are also limited laboratory data to support the use of HXLPE in the ankle.…”
Section: Introductionmentioning
confidence: 99%